Jan Wnęk, Polska myśl pedagogiczna 1795-1863, Kraków 2007, ss. 295 Wyd. MCDM - Markiewiczowa, Hanna (Biuletyn Historii Wychowania, 2008)
Jan Wnęk, Polska myśl pedagogiczna 1795-1863, Kraków 2007, ss. 295 Wyd. MCDM